Cytochrome c Release From Oridonin-Treated Apoptotic A375-S2 Cells Is Dependent on p53 and Extracellular Signal-Regulated Kinase Activation - Chun-Ling Zhang; Li-Jun Wu; Hai-Jun Zuo; Shin-ichi Tashiro; Satoshi Onodera; Takashi Ikejima (Elsevier, 2004)
We have reported that oridonin isolated from Rabdosia rubescens induces apoptosis of human melanoma A375-S2 cells within 12 h. In this study, TUNEL assay and flow cytometric analysis also indicate that one of the causes of A375-S2 cell death induced by oridonin was apoptosis. The cell death was preceded by the release of cytochrome c from the mitochondria. Twelve hours after treatment with oridonin, the ratio of Bax/Bcl-xL protein expression was increased and release of cytochrome c was decreased by an extracellular signal-regulated kinase (ERK) MAPK inhibitor (PD98059) and a phosphoinositide 3-kinases (PI3-K) inhibitor (wortmannin). A mitochondrial permeability transition (MPT) inhibitor, decylubiquinone, suppressed the release of cytochrome c without affecting Bax expression. The activation of p53 by oridonin was also blocked by wortmannin. In addtion, PD98059 and wortmannin significantly decreased oridonin-induced DNA fragmentation, but the p38 MAPK inhibitor (SB203580) did not after DNA fragmentation. Oridonin induced A375-S2 cell apoptosis by activating parallel p53 and ERK pathways, increasing the ratio of Bax/Bcl-xL protein expression, and promoting the release of cytochrome c into the cytosol, resulting in apoptotic cell death. Keywords:: oridonin, Bax/Bcl-xL, cytochrome c, P53, extracellular signal-regulated kinase